Vehicle license plate recognition systems: article / Imran Ismail - Ismail, Imran (2004)
The purpose of the vehicle license plate recognition project is to recognize or identify vehicles. Vehicle license plates are meant to be recognized by people, especially government officials such as policemen and transport personnel. In current situation, we can identify all the information’s related to the drivers from plate number. Vehicle’s license plates that are authorized are allowed to enter the campus premises. In this project, a database of vehicle license plate numbers that are authorized to enter the university grounds has been compiled. Only these vehicles are allowed to enter the campus.